International R&D Partnerships Between Companies: A Computational Study - Alghamdi, Mohamad (Communications in Mathematics and Applications, 2023)
This paper contributes to the empirical study of the cooperation of companies in research and development (R&D). The contribution is based primarily on the consideration of all industrial sectors under all types of agreements at the domestic and international levels. The outcomes suggest that active companies in the cooperation system played an important role in forming overlapping structures. In particular, the cooperation of those companies included domestic and international agreements and served multiple sectors.